Pengaruh Pendekatan Pembelajaran Matematika Realistik Terhadap Hasil Belajar Matematika Ditinjau dari Minat Komputasi Siswa - Ngakan Putu Sindu Wija Putra (Edukasi: Jurnal Pendidikan Dasar, 2021)
This study aims to find out the effect of Realistic Mathematics Education toward mathematic learning result of students in grade III Elementary School Students II Gianyars Subdistrict. The results showed that. (1) there was a difference in learning outcomes of Mathematics between groups of students who followed Realistic Mathematics Education and groups of students following the conventional learning. (2) there is an interaction effect between the learning model and the computation interest toward the learning outcomes of Mathematics. (3) there are differences in learning outcomes of Mathematics between groups of students who follow the Realistic Mathematics Education and groups of students who follow conventional learning in groups of students who have high computation interest and vice versa.